Threatened in the making: institutional consolidation and precariousness in the independent performing arts in Europe. Issue 1 (2nd January 2023) - Eder, Thomas Fabian
ABSTRACT: The independent performing arts are establishing themselves as an independent organizational field operating across Europe. The focus is not on artistic form or aesthetics, but on structural and organizational features that define the field institutionally in many countries of Northern, Eastern, Southern and Western Europe alike. The presented consideration of these features is specified in an analysis of the socio-economic situation in the field, especially in light of the new challenges of the Coronavirus pandemic. Subsequently, the actions taken by different advocacy groups to improve the precarious situation across countries and their effectiveness in governance are described to illustrate international coalition patterns, the development of mutual awareness and isomorphic alignment in the structuring of the field beyond nation-state borders. The research is based on 1031 survey responses from artists and cultural professionals as well as expert interviews with the management staff of the interest groups of independent performing arts from 12 European countries (This paper is an elaboration of the following work published in French: Eder, Thomas Fabian. 2022. "Rapport Intermédiaire : Les Arts Du Spectacle Indépendants Entre Consolidation Institutionnelle et Précarité – Une Perspective Comparative Européenne." D'Allemagne d'Aujourd'hui (No 241)).